Return to sport guidelines in athletes with selected acute respiratory infections, including COVID-19, based on clinical criteria and laboratory investigations - Schwellnus, Martin Peter (University of Pretoria, 2023)
Thesis (PhD (Sports Medicine))--University of Pretoria, 2023.